Achievement of Blood Pressure Targets and Safety of Azilsartan Medoxomil/Chlorthalidone Fixed Dose Combination versus Azilsartan Medoxomil in Hypertensive Patients Uncontrolled on Monotherapy. (June 2015) - Juhasz, A.; Collier, D.; Caulfield, M.; Agabiti-Rosei, E.; Huang, P.; Hisada, M.; Zhao, L.; Kupfer, S.
Abstract : Despite the availability of potent antihypertensive medicines, achieving blood pressure control with good tolerability remains challenging. The efficacy and safety of azilsartan-medoxomil (AZL-M)/chlorthalidone (CLD) combination at 40/12.5 and 40/25 mg were assessed against AZL-M/Plbo 40/0 mg in a randomized, double-blind (DB) study. Grade 2–3 essential hypertensive patients with post-placebo mean clinic SBP 160–190 mmHg and 24 h SBP 140–175 mmHg by ABPM were administered 40 mg AZL-M for 4 weeks. Less than 10% of patients on 4-week monotherapy achieved target SBP < 140 mmHg. "Non-responders" were then randomized to 8 weeks of DB treatment with AZL-M/Plbo 40/0 mg, AZL-M/CLD 40/12.5 or AZL-M/CLD 40/25 mg. After 8 weeks, target SBP and DBP (<140/90 [or < 130/80 mmHg for those with DM or CKD]) were achieved in 35.3 and 60.2% of subjects on monotherapy; 62.7 and 81.0% with AZL-M/CLD 40/12.5 mg, and 77.8% and 85.9% with AZL-M 40/25 mg, respectively (p ⩽ 0.001). Increased creatinine was observed in 8.1% of patients on AZL-M/CLD 40/25, versus 3.1 and 3.0% of those receiving AZL-M/CLD 40/12.5, and AZL-M/Plbo 40/0 mg. Study drug discontinuation was higher in the AZL-M/CLD 40/25 mg (6.7%) than in the AZL-M/CLD 40/12.5 mg or AZL-M/Plbo 40/0 mg groups (2.4 and 2.3%). No clinically relevant changes were observed for electrolytes (including potassium), hepatic enzymes, hematology or urinalysis parameters. Uric acid increase was observed at a slightly higher rate in the AZL-M/CLD groups without increase in gout-related events. AZL-M/CLD is highly effective and well tolerated in patients who don't achieve blood pressure goals with AZL-M monotherapy.